PALAEOECOLOGIC AND PALAEOBIOGEOGRAPHIC CHARACTER OF MIDDLE PLIOCENE NON-MARINE MOLLUSC FAUNAS FROM NORTH-WESTERN ITALY (Rivista italiana di Paleontologia e Stratigrafia, 2004)
Significant new records of rich Middle Pliocene nonmarine mollusc assemblages from the Piedmont basin (North-western Italy) have led to an update of the systematic position of some taxa known since the end of the 19th century. The recorded molluscs come from deposits belonging to the San Martino unit in the "Villafranchian type-area" (Villafranca d’Asti) and to Cuneo and Alessandria districts. Vertebrate remains referred to the Middle Pliocene Triversa Faunal Unit (Mammal Neogene zone MN16a) are often associated with molluscs. A detailed palaeoecologic and palaeobiogeographic picture of the Middle Pliocene aquatic and terrestrial mollusc faunas is outlined. The assemblages are characterised by a high degree of species diversity and by the dominance of land prosobranchs and pulmonates. The palaeoecologic character is related to the different sedimentary facies recognised in the lithostratigraphic units: hygrophilous land faunas in paleosols and dominant aquatic taxa in lacustrine-palustrine sediments. Thermophilous swampy and forest taxa point to warm-temperate and humid climate conditions. A high number of extinct taxa and a high rate of endemism are underlined. A Mio-Pliocene Central-western European origin is noticed for many species. In the Middle Pliocene a spreading of some terrestrial species took place from North-western Italy towards Central Italy. Some new extinct taxa, belonging to the families Aciculidae (Renea sp. 1) and Clausiliidae [Monoptychia (subgen. n.) sp. 1; Neostyriacasp. 1; Fusulus (Fusulus) sp. 1], are identified.